Challenges and Prospects of New Plant Breeding Techniques for GABA Improvement in Crops: Tomato as an Example - Gramazio, Pietro; Takayama, Mariko; Ezura, Hiroshi (Frontiers in Plant Science, 2020)
Over the last seven decades, γ-aminobutyric acid (GABA) has attracted great attention from scientists for its ubiquity in plants, animals and microorganisms and for the physiological implications as a signaling molecule involved in multiple pathways and processes. More recently, also the food and pharmaceutical industries have significantly increased interest in GABA, in virtue of the great potential benefits for human health and the consumers demand for health-promoting functional compounds, releasing a plethora of GABA-enriched products. Nevertheless, many crop species accumulate appreciable GABA levels in their edible parts and could help to meet the daily recommended intake of GABA for promoting health positive effects. Therefore, plant breeders are devoting many efforts to breed elite varieties with improved GABA content. In this regard, tomato (Solanum lycopersicum) has received much consideration for accumulating remarkable GABA levels, being the most produced and consumed vegetable worldwide and a fruit-bearing model crop. Even though many different strategies have been implemented, from classical crossbreeding to induced mutagenesis, the new plant breeding techniques (NPBTs) have achieved the best results to accumulate GABA in red ripe tomato fruits along with shedding the light on GABA metabolism and gene functions. In this review, we summarize, analyze and compare all the studies that have substantially contributed to tomato GABA breeding and overview and propose the most recent NPBTs that could bring this process to the next level of precision and efficiency. This document also intends to serve as guidelines for other crops to take advantage of the progress achieved in tomato for more efficient GABA breeding programs.